Prisons and punishment in America: examining the facts - O'Hear, Michael (Contemporary debates, 2024)
"After three decades of explosive growth, the American incarceration rate is impracticably high. Drawing on leading research in law and the social sciences, this book covers a range of topics in sentencing and corrections in America in a manner that is accessible and engaging for general readers. Tackling high-level issues in the criminal justice system, it outlines the scale and causes of mass incarceration in the United States. To complement this, it details the roles and relative power of judges and prosecutors, the severity of punishment for drug offenders and white-collar offenders, the abuse of prisoners and the enforcement of prisoner rights, and repeat offending by released prisoners. Readers will better understand the challenges that come with a high incarceration rate, such as the management of mental illness in the criminal justice system, the management of sex offenders, and the impact of parental incarceration on children. Looking ahead, this timely resource also considers prospects for reducing current incarceration levels, the availability and effectiveness of alternatives to incarceration, and the future of capital punishment" --